1997
DOI: 10.1042/cs0920247
|View full text |Cite
|
Sign up to set email alerts
|

Na+,K+-ATPase Expression in Maleic-Acid-Induced Fanconi Syndrome in Rats

Abstract: Na+,K(+)-ATPase activity and its alpha 1 subunit protein and mRNA in kidney cortex were monitored in rats developing Fanconi syndrome after the administration of maleate. Na+,K(+)-ATPase activity was significantly lower than in saline-injected controls, although this was partially mediated by a general, non-specific decrease in the cortex protein content. 2. The low activity of the sodium pump correlated with low abundance of alpha 1 subunit mRNA and protein levels. Hsp60 protein levels were also decreased in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…Most solute transport, including bicarbonate, phosphate, amino acids, and glucose, is mediated by Na + ‐coupled mechanisms. The effectiveness of Na + ‐dependent transport depends on the maintenance of a low intracellular sodium concentration, and the basolateral Na + ,K + ‐ATPase plays the major role in maintaining this process [7, 8, 45]. The failure of proximal sodium transport, that leads to a global failure in reabsorption, has been shown in an experimental model of FS induced by maleic acid [8, 45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most solute transport, including bicarbonate, phosphate, amino acids, and glucose, is mediated by Na + ‐coupled mechanisms. The effectiveness of Na + ‐dependent transport depends on the maintenance of a low intracellular sodium concentration, and the basolateral Na + ,K + ‐ATPase plays the major role in maintaining this process [7, 8, 45]. The failure of proximal sodium transport, that leads to a global failure in reabsorption, has been shown in an experimental model of FS induced by maleic acid [8, 45].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical efficacy of IFO is greatly limited because of its severe cytotoxic side effects including hemorrhagic cytitis and nephrotoxicity [6]. Proximal tubular impairment is the most common feature of toxicity, which frequently presents as Fanconi syndrome (FS) with a generalized increase in organic solute and ion excretion resulting in polyuria, glucosuria, aminoaciduria, proteinuria, calciuria and phosphaturia [7, 8], these changes are a result of a number of reabsorptive and secretory transport defects, mainly of Na + ‐dependent transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Published work reported that exposure to high doses of MA result in phenotypic manifestations such as alopecia and significant decreases in both absolute and relative organ weights (Burnett et al, ). Upon consumption, the absorbed and metabolized MA become nephrotoxic and cause symptoms such as phosphaturia, glycosuria, low molecular weight proteinuria, metabolic acidosis and aminoaciduria (Castano, Marzabal, Casado, Felipe, & Pastor‐Anglada, ; Shikano et al, ). The aforementioned damages to the proximal renal tubules of the kidney, collectively known as Fanconi syndrome, can result in cell necrosis and renal tubular injury in the proximal tubules (Bunton, Fuller, Perry, & Shiner, ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, a wide range of past studies have already indicated that the consumption of maleic acid can cause kidney damage . However, most of those studies discussed the damage caused to renal tubules.…”
Section: Introductionmentioning
confidence: 99%